2012
DOI: 10.1016/j.foodchem.2011.11.145
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effect of whole lupin (Lupinus albus) seed and its protein isolate

Abstract: This study describes the hypocholesterolaemic effect of whole lupin and its protein in hamsters. The diets were: casein (control group HC), lupin protein isolate (group HPI) and whole lupin seed (group HWS). Diets from HPI and HWS promoted a significant reduction of total cholesterol and non-HDL cholesterol in the hamsters' plasma as compared with HC. The true digestibility of HPI and HC groups were similar and differed significantly from the HWS one, which in turn showed a significant difference in total ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 41 publications
3
45
0
6
Order By: Relevance
“…One-way analysis of variance (ANOVA) and Tukey's post hoc test were performed to test the significance of differences (P < 0.05) between groups (Gustavo, José, Robison, Paulo, & José, 2012). The statistical analyses were carried out using Minitab software version 14.13 (USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-way analysis of variance (ANOVA) and Tukey's post hoc test were performed to test the significance of differences (P < 0.05) between groups (Gustavo, José, Robison, Paulo, & José, 2012). The statistical analyses were carried out using Minitab software version 14.13 (USA).…”
Section: Discussionmentioning
confidence: 99%
“…It could be seen from the obtained results that adding germinated SWL oil and extracted flour enriched biscuits to the diet could produce significant improvement for the beneficial lipoprotein ratios to reduce the risk of heart disease in hyperlipidemic individuals. Gustavo, José, Robison, Paulo and José (2012) demonstrated that protein isolate from Lupinus albus has a metabolic effect on endogenous cholesterol metabolism and a protector effect on the development of hepatic steatosis. Whereas, El-Malky and Gouda (2007) indicated that germinated lupin seeds reduced the hepatic enzymes ALT and AST and avoided the damage in liver tissues resulted from hyperlipidemic diet effect compared to the positive control.…”
Section: Predictors Of Coronary Riskmentioning
confidence: 99%
“…As such, in current management of diabetes, statins are included to control the dyslipidemia. Indeed, hypolipidemic and anti-atherosclerotic effects of L. albus were demonstrated in high-fat diet fed animals (Fontanari et al, 2012;Marchesi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As such, in current management of diabetes, statins are included to control the dyslipidemia. Indeed, hypolipidemic and anti-atherosclerotic effects of L. albus were demonstrated in high-fat diet fed animals (Fontanari et al, 2012;Marchesi et al, 2008).We therefore set out to investigate the effects of crude aqueous extract of L. albus in non diabetic and beta cell depleted streptozotocin (STZ)-induced type 1 diabetic rats. The rationale for using the aqueous extract is because alkaloids and peptides, components already demonstrated to have hypoglycaemic and hypolipidemic effects, are highly soluble in water.…”
mentioning
confidence: 99%
“…A dieta com 13,5 % de gordura saturada e 0,1 % de colesterol induziu a hipercolesterolemia nos grupos em que estas fontes lipídicas foram adicionadas (controle, farinha de jatobá in natura e farinha de jatobá extrusada), conforme esperado e já relatado em estudos prévios conduzidos com o mesmo delineamento experimental (FROTA et al, 2008;DIAS, 2012;FONTANARI et al, 2012).…”
Section: Perfil De Lipídeos Séricosunclassified